(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Despite the high level of modern technologies in the field of laboratory methods and radiation imaging of the respiratory organs, the problem of early and accurate differential diagnosis of inflammatory lung diseases remains important in practical medicine. Purpose of the study: to study the features of radiological data of patients with chronic lung abscess.